Choosing on influence - Tugce Cuhadaroglu (Theoretical Economics, 2017)
Interaction, the act of mutual influence, is an essential part of daily life and economic decisions. This paper presents an individual decision procedure for interacting individuals. According to our model, individuals seek influence from each other for those issues that they cannot solve on their own. Following a choice-theoretic approach, we provide simple properties that aid us to detect interacting individuals. Revealed preference analysis not only grants underlying preferences, but also the influence acquired.
Keywords: D01; D03; D11; 330; Interaction; social influence; boundedly rational decision making; two-stage maximization; incomplete preferences